Biochemical and Physiological Insights into Adipokine-Mediated Insulin Resistance and Its Association with Atherosclerotic Progression in Prediabetic Patients - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Insulin resistance is a key metabolic abnormality in prediabetes that contributes to the development of type 2 diabetes mellitus (T2DM) and accelerates atherosclerosis. Adipose tissue functions as an endocrine organ, secreting adipokines that regulate insulin sensitivity, vascular function, and inflammation. Altered adipokine profiles may provide mechanistic links between prediabetes and early atherosclerotic changes. Objectives: To investigate the biochemical and physiological insights into adipokine-mediated insulin resistance and its association with atherosclerotic progression in prediabetic patients. Methodology: This cross-sectional study was conducted from December 2022 to August 2023 at Nawaz Shareef Medical College, Aziz Bhatti Shaheed Teaching Hospital, Gujrat, and Chahudhary Pervaiz Elahi Institute of Cardiology, Wazirabad. A total of 100 prediabetic patients were enrolled. Demographic data, anthropometric measurements, and blood pressure were recorded. Fasting glucose, insulin, lipid profile, hs-CRP, adiponectin, leptin, resistin, visfatin, and TNF-α were measured. Insulin resistance was assessed using HOMA-IR. Carotid intima-media thickness (CIMT) was determined by B-mode ultrasonography. Statistical analysis included correlation and regression models. Results: Participants had elevated HOMA-IR, dyslipidemia, and raised hs-CRP. Adiponectin levels were significantly reduced, while leptin, resistin, visfatin, and TNF-α were increased. CIMT was higher in 28% of patients, indicating early atherosclerosis. Adiponectin showed an inverse correlation with CIMT, whereas leptin, resistin, visfatin, TNF-α, and hs-CRP correlated positively. Conclusion: Prediabetic patients demonstrate a dysregulated adipokine profile and inflammatory state that are strongly associated with early subclinical atherosclerosis. Monitoring adipokines may serve as an early tool for cardiovascular risk stratification and prevention in high-risk populations. Keywords: Prediabetes; Insulin resistance; Adipokines; Atherosclerosis; Inflammation; Carotid intima-media thickness